Digital Fiscal Government and State Financial Data Protection: A New Legal Framework for Digital Auditing in Indonesia - KMS Herman; Iqbal Ramadhan; Pan Panissa Barlian Barlian; Surya Surya; Hendry Juanda (Jurnal Greenation Sosial dan Politik, 2026)
The digital transformation of public administration has significantly altered the management of state finances in Indonesia. The integration of information technology into budgeting, revenue collection, expenditure management, and financial reporting has given rise to the concept of digital fiscal government, which relies on data-driven governance to improve efficiency, transparency, and accountability. Alongside these developments, the increasing dependence on digital systems has generated new legal challenges concerning the protection of state financial data, particularly within the implementation of digital auditing. Existing regulations governing public finance, electronic systems, and data protection remain fragmented and have not yet established a comprehensive legal framework capable of addressing the complexities of digital audits. This study aims to examine the development of digital fiscal government in Indonesia, identify legal issues related to the protection of state financial data in digital auditing, and formulate a legal framework that supports effective and accountable digital audit practices. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. Legal materials are analyzed qualitatively through the interpretation of legislation, legal doctrines, and relevant scholarly works concerning public finance governance, digital government, and data protection. The findings indicate that the rapid digitalization of fiscal administration has not been accompanied by specific regulations governing digital auditing. This regulatory gap creates legal uncertainty regarding data access authority, cybersecurity standards, accountability for technology-based audit mechanisms, and the protection of strategic state financial information. Furthermore, the growing use of data analytics and artificial intelligence in auditing raises concerns regarding transparency, reliability, and legal responsibility for algorithm-based decisions. Therefore, a new legal framework is required to integrate principles of state financial data protection, cybersecurity, technological accountability, and digital governance. Such a framework is essential to ensure legal certainty and strengthen the effectiveness of digital auditing within Indonesia’s evolving fiscal governance system.